A Mechanism-Centred Approach to Evaluating Complex Aid Interventions: The Case of Accompanying Measures to Budget Support - Schmitt, Johannes; Krisch, Franziska (Journal of MultiDisciplinary Evaluation, 2017)
Background: Current methodological debates related to theory-based evaluations (TBE) centre around questions how to improve the explanatory strength of these approaches and how to integrate mechanisms as analytic concept. Particularly in complex aid interventions, when multiple elements are expected to interact and thus create an added value, exploring mechanisms as an analytical tool can be promising. Purpose: This paper seeks to contribute to the discussion on the use of TBE for evaluating complex aid interventions by sharing experiences from a recent evaluation of accompanying measures to general budget support. Setting: Nine countries of sub-Saharan Africa which have received German budget support, namely Burkina Faso, Ghana, Malawi, Mali, Mozambique, Rwanda, Tanzania, Uganda, Zambia. Intervention: Accompanying measures (mainly in the form of technical assistance and capacity development) are one element of the budget support package, which further encompasses financial contributions, policy dialogue, and conditionalities. Research Design: We focus on interrelations between different elements of budget support and apply a mechanism-centred approach to programme theory building, Data Collection and Analysis: After defining accompanying measures and integrating them into the intervention logic of budget support used in recent multi-donor evaluations, key mechanisms were identified on an explorative mission to Mozambique, validated in an online survey, and further discussed in expert interviews and during field research in Tanzania. Findings: For the specific example relating to two elements of budget support (policy dialogue and accompanying measures), some of the hypothesized mechanisms were found to create an added value and thus increase the effectiveness of budget support as a package. The applied approach helped generate a more comprehensive implementation theory and provided insights into potential benefits and challenges of combining different elements in one programme. Beyond its use for future evaluations in the field of budget support, we argue that TBE of complex interventions can benefit from adopting such a mechanism-centred approach to create a better understanding of how different elements of the programme interact. Moreover, the focus on mechanisms when analysing programme implementation enables evaluators to improve their empirical inquiry on the identified mechanisms and to draw valid conclusions on the programme’s contribution to the observed outcomes.